Groin Pain Syndrome : A Multidisciplinary Guide to Diagnosis and Treatment - Zini, Raul; Volpi, Piero; Bisciotti, Gian Nicola (Springer International Publishing : Imprint: Springer, 2017)
This book provides accurate descriptions of the injuries responsible for groin pain, which tend to occur in association with particular sports. The approach is multidisciplinary, ensuring that the book will be of broad appeal, and the focus is especially on epidemiology, etiology, and possible treatment options. Throughout, care has been taken to depict the state of the art in this constantly evolving field. A new classification of groin pain syndrome is presented, and the coverage encompasses hip, visceral, tendon/muscle, bone, and neurologic pathology. In addition, guidance is provided in selection of the rehabilitation program that will best meet the patient's needs, taking into account individual circumstances. Groin pain is among the most prevalent lower limb symptoms. The pain may occur immediately after an injury or develop gradually and is often exacerbated by continued use of the injured area. In presenting the latest knowledge on groin pain syndrome and its management, this book will be of value to a range of practitioners, including sports medicine specialists, primary care providers, urologists, orthopedists, and physiatrists. .
Keywords: Medicine.; Orthopedics.; Rehabilitation.; Sports medicine.; Physiotherapy.; elektronické knihy; electronic books